2018
DOI: 10.3889/oamjms.2018.344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diagnostic Efficiency of Alpha-Fetoprotein in Patients with Liver Cirrhosis and Hepatocellular Carcinoma: Single-Center Experience

Abstract: BACKGROUND:AFP serum levels are considered as diagnostic and specific for hepatocellular carcinoma (HCC) in patients with liver cirrhosis (LC).AIM:This study aimed to examine the diagnostic value of AFP in the distinguishing of patients with HCC from patients with LC, and to analyse the potential correlation between AFP levels and liver disease stages.MATERIAL AND METHODS:Fifty patients with LC and fifty patients with HCC were included in this study. The majority of the patients were males, while the HBV aetio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…In the current study, there was a significant increase in AFP level in the HCC group when compared to control and CAH groups ( p value = 0.001). This result is in agreement with other studies ( Mehinovic et al, 2018 ), ( Shalably et al, 2019 ), ( Ibrahim et al, 2018 ). The increase in secretion of AFP during the development of HCC to inhibit immune response of liver cancer cells caused by increasing in selective transcriptional activation in AFP gene in the malignant hepatocytes showed by ( Wu et al, 2006 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the current study, there was a significant increase in AFP level in the HCC group when compared to control and CAH groups ( p value = 0.001). This result is in agreement with other studies ( Mehinovic et al, 2018 ), ( Shalably et al, 2019 ), ( Ibrahim et al, 2018 ). The increase in secretion of AFP during the development of HCC to inhibit immune response of liver cancer cells caused by increasing in selective transcriptional activation in AFP gene in the malignant hepatocytes showed by ( Wu et al, 2006 ).…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, we found in this context that the diagnostic performance of AFP as a marker for differentiating HCC from benign liver diseases and healthy candidates revealed that the diagnostic sensitivity was 80%, the specificity was 90%, PPV was 90% and NPV was 80% and accuracy was 80%, as shown in ( Table 3 ) that is not far from the results of ( Ibrahim et al, 2018 )who reported that sensitivity of HCC is (75%) and specificity was (100%). Another study by ( Mehinovic et al, 2018 ) reported that AFP has sensitivity, and specificity ranges from 39% to 97%, and 76% to 95%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Mehinovic et al 10 aimed to evaluate the diagnostic value of AFP in estimation of patients with HCC from cirrhotic patients and also to analyze the potential correlation between AFP levels and stages of liver cirrhosis. Their study included 50 patients with HCC and 50 patients with liver cirrhosis.…”
Section: Figurementioning
confidence: 99%
“…In accordance with these studies, AFP in our study showed poor power to discriminate HCC from CLD patients. In contrast to these reports, Mehinovic et al [53] found that AFP is a good biomarker to diagnose HCC patients. AFP specificity is affected by patient sex and race [54] which may partly explain this discrepancy in findings.…”
Section: Discussionmentioning
confidence: 83%